Surgical Determinants of Post Operative Pain in Patients Undergoing Laparoscopic Adnexectomy. Issue 6 (1st June 2022) - Ebanga, Lea; Dabi, Yohann; Benichou, Jeremie; Miailhe, Gregoire; Kolanska, Kamila; Uzan, Jennifer; Ferrier, Clement; Bendifallah, Sofiane; Haddad, Bassam; Darai, Emile; Touboul, Cyril
Abstract: Objective: The objective of our study was to determine the main surgical factors associated with postoperative pains in patients undergoing adnexectomy. Material and Methods: Patients that underwent adnexectomy in two French Gynecological centers between July, 2018 and March, 2020 were prospectively included and retrospectively analyzed. The main pre and per operative surgical factors were analyzed to assess their impact on immediate postoperative pain. Analgesic consumption was recorded for each patient and pain was evaluated using the validated numeric rating scale (ranging between 0 and 10). Results: One hundred and seventeen patients underwent laparoscopic adnexectomy. Eighty-four patients (72%) experienced either no or minor postoperative pain (NRS ≤ 2). Seventeen patients (14.5%) required strong opioids (subcutaneous morphine injection) in the immediate postoperative period. The only two parameters that had a significant impact on immediate postoperative pain were the realization of a fascia closure and the duration of pneumoperitoneum longer than 60 minutes. Pneumoperitoneum pressure and size of ports were not significantly correlated with postoperative pain. Conclusion: Fascia closure and increased surgical time were significantly associated with immediate postoperative pain and the need for strong opioids consumption. Surgical training to limit prolonged surgeries should be strongly emphasized to lower postoperative pain and limit opioids consumption.